Biphenyl-type neolignans with NO inhibitory activity from the fruits of Magnolia tripetala. (August 2021) - Nie, Wei; Ding, Lin-Fen; Lei, Tie; Liu, Zhen-Xiang; Li, Jin-Da; Song, Liu-Dong; Wu, Xing-De
Graphical abstract: Highlights: Two new biphenyl-type neolignans were isolated from Magnolia tripetala. Tripetalin A was a magnolol-honokiol-type neolignan dimer linked by C-5′‒C-5′′ bond. Magnoquinone and magnotriol B displayed noteworthy NO inhibitory activity. Abstract: Tripetalins A (1 ) and B (2 ), two new biphenyl-type neolignans were obtained from the fruits of Magnolia tripetala, along with four known analogues. The structures of the new compounds were characterized by comprehensive spectroscopic analyses including 1 H, 13 C, and 2D NMR, IR, and HRESIMS data. Tripetalin A (1) was the first magnolol-honokiol-type neolignan dimer linked through C-5′‒C5′′ carbon bond. Magnoquinone (5 ) and magnotriol B (6) displayed remarkable NO inhibitory activity with IC50 values of 4.52 ± 0.07 and 2.02 ± 0.03 μ M, respectively.